(untitled) (Medicine Today, 2019)
Introduction: This study aimed to identify the risk factors for abnormal semen parameters in male partner of sub-fertile couples. Materials & Methods: This was a prospective study of 100 diagnosed infertile & sub-fertile couples in the age group between 23-58 yrs old male were from 1st March 2013 to 28th Feb 2014 treated in Dhaka Combined Military Hospital (CMH). On the basis of sperm count the cases were grouped as follows. normozoospermia, oligozoospermia & azoospermia. Semen analysis was done in all the cases, The results were described with arithmetic mean and standard deviation. Male partners with normal semen parameters was undertaken among the sub-fertile couples attending the General Outpatient Department (GOPD) of CMH Dhaka. The history was taken from selected individual and it includes personal, socio-economics, occupational, medical, surgical history and drug intake to find out risk factors for abnormal semen parameters. Results: In Normozoospermia mean and SD of sperm count, sperm abnormally, sperm motillity were 65.98±5.05, 24.44±1.57 and 45.5±2.94 respectively. In 0ligozoospermia the mean and SD of sperm count, sperm abnormality, sperm mtility were 7.74±1.23, 41.1±3.78, 14.54±2.77 respectively. In azoospermia the mean and SD of sperm count, sperm abnormality, sperm motility were absent. Conclusion: Here data statistically showed person with normozoospermia having good sperm morphology & motility than oligozoospermia and azoospermic subjects thereby causing male infertility which was responsible for hindrance in achieving pregnancy clinically. Using tight undergarment or working in hot atmosphere depresses spermatogenesis. Mumps orchitis permanently damage spermatogenesis. Bacterial or viral infection depresses the sperm count. Diabetes, malnutrition, heavy smoking reduces spermatogenesis. β-blocker, antihypertensive were likely to hinder spermatogenesis. The efferent ducts might be obstructed by infection like tubercular, gonococcal or by surgical trauma. Medicine Today 2019 Vol.31(1): 31-35